Effect of Liquid Smoke Treatment on Banana Stem Fibers as Composite Reinforcement - Muslimin, Mukhlis; Seng, Ahmad; Latif, Lita Asyriati; Harbelubun, Mohammad Muzni; Umar, Kifli; Ramli, Eat (SAINSTECH NUSANTARA, 2025)
This study aims to identify the potential utilization of banana stem fiber (BSF) as a locally sourced composite material to support building infrastructure in North Maluku. The research focuses on analyzing the tensile and impact properties of the composite. An experimental method was used, incorporating different treatment durations for the fibers by immersing them in liquid smoke for 1, 2, and 3 hours. The treated fibers were then heated at 40°C for 30 minutes. The next step involved fabricating BSF-reinforced composite specimens by preparing the resin and fibers, with a fiber length of 10 mm and a composition of 30% BSF and 70% resin. Tensile and impact tests were conducted to evaluate the mechanical properties of the composites. The results showed that the tensile strength of the P3J composite increased to 88.351 MPa, representing a 3.79% improvement compared to the untreated composite (TP). Meanwhile, the impact strength showed the highest increase after 1 hour of immersion, reaching 10.911 KJ/m, which is 25.45% higher than TP. These findings indicate that liquid smoke treatment enhances the tensile and impact properties of the composite.